Porphyromonas Gingivalis May Seek the Alzheimer’s Disease Brain to Acquire Iron from Its Surplus - Olsen, Ingar (J Alzheimers Dis Rep, 2021)
Iron accumulates in the brain of subjects with Alzheimer’s disease (AD). Here it promotes the aggregation of amyloid-β plaques in which it is abundant. Iron induces amyloid-β neurotoxicity by damaging free radicals and causing oxidative stress in brain areas with neurodegeneration. It can also bind to tau in AD and enhance the toxicity of tau through co-localization with neurofibrillary tangles and induce accumulation of these tangles. Porphyromonas gingivalis is a key oral pathogen in the widespread biofilm-induced disease “chronic” periodontitis, and recently, has been suggested to have an important role in the pathogenesis of AD. P. gingivalis has an obligate requirement for iron. The current paper suggests that P. gingivalis seeks the AD brain, where it has been identified, to satisfy this need. If this is correct, iron chelators binding iron could have beneficial effects in the treatment of AD. Indeed, studies from both animal AD models and humans with AD have indicated that iron chelators, e.g., lactoferrin, can have such effects. Lactoferrin can also inhibit P. gingivalis growth and proteinases and its ability to form biofilm.